A Yogic Dynamic Executive Function Frame Work for Linking Attention, Adjustment and Cognitive Flexibility of School Children - Mishra, Ankita; Gowda, G. Paran (Challenges in Disease and Health Research Vol. 9, 2021)
In the age group of 5 to 13 years school going children there is always a fast growth of Executive Function (EF) parts of the brain. The EF growth gets shunted in the given school environment, where the growing genes of the children and their syllabus plays a major role. During this period, the children are loaded with heavy school curriculum and thus limiting the learning processes and creatively get lost in curriculum based growth. In this paper we propose to strengthen the EF, functioning through a complimentary Yoga frame. This new frame gives us a protocol of yoga techniques to improve, the Attention, Adjustment and Cognitive flexibilities of the mind. Supplementation of yoga along with curriculum inculcates the habit of cognitive aspects of the brain which will make their carriers useful and betterment of the society. Yoga frame for children mediates the link between school curriculum and with EF resulting into better outputs underlying benefits of yoga. The yoga practices will help the individual EF of the child to grow and step into adolescent age.